Preferential orientation and surface oxidation control in reactively sputter deposited nanocrystalline SnO2:Sb films: Electrochemical and optical results - Montero, José; Guillén, Cecilia; Granqvist, Claes G.; Herrero, José; Niklasson, Gunnar A. (The Electrochemical Society, 2014)
Antimony doped tin oxide is a versatile transparent electrical conductor. Many of its properties depend on the electronic band structure at the surface of a thin film–such as the position of the Fermi level, ionization potential Ip, optical gap energy, etc.–which in its turn is related to the surface termination given by the crystallographic orientation of the film. We prepared SnO2:Sb films by reactive DC magnetron sputtering at different oxygen/argon ratios and found by X-ray diffraction that the crystallographic orientation could be changed from tetragonal (101) to tetragonal (110) as the oxygen content was raised. Electrochemical measurements showed that this change in preferential orientation was accompanied by an increase of Ip by more than 1 eV as a result of the modification of the oxidation state of tin atoms at the film’s surface. Such alterations of Ip have a large impact on the electrochemical, photocatalytic and gas sensing behavior of the material. Moreover, preferential orientation control–and hence Ip tuning–allow the tailoring of SnO2:Sb electrodes for various application by reducing the Schottky barrier.
Keywords: sputtering; thin films